The Role of the North Sumatra Quran History Museum in Efforts to Preserve Illuminated Manuscripts of the Quran - Hafiz Zuhdi; Achiriah; Intan Ali Lubis; Sri Ramadini Tanjung; Khairani Rangkuti; M. Alfarisi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The Quran manuscripts have a very important role in the development of the writing of the Quran from time to time. To maintain and preserve the Illuminated Quran Manuscripts in North Sumatra, various efforts have been made to collect the manuscripts by Mr. Dr. Phil Ichwan Azhari. One of them is by establishing the North Sumatra Quran History Museum. The role of the North Sumatra Quran Museum is very important in the conservation and preservation of illuminated Quran manuscripts. There are sixteen illuminated Quran manuscripts in this museum, including the East Coast illuminated manuscript, Malay-Aceh illuminated manuscript, Sunflower illuminated manuscript, Javanese illuminated manuscript, Tumpal Floral illuminated manuscript, the oldest manuscript with 1070 H/1074 H Colopon, two-syp illumination, Floral-Geometric illumination, three juz of the ancient Quran manuscript, four juz of the ancient Quran manuscript, two juz of the ancient Quran manuscript, and five juz of the ancient Quran manuscript. This study aims to examine the role and efforts of the North Sumatra Quran History Museum in preserving the illuminated Quran manuscript. The research method used in this study is a descriptive qualitative approach by conducting direct observation, interviews and documentation of the research object. The findings of this study indicate several roles of the museum, namely as an institution that manages, collects, maintains, records and preserves ancient, illuminated manuscripts. The role and efforts of the Museum in preserving ancient, illuminated manuscripts by means of procuring or adding to collections, conservation, protection, development, utilization, research and holding public events through visits by school children and students.